PREVALENCE OF IMPACTED MANDIBULAR AND MAXILLARY THIRD MOLARS: A RADIOGRAPHIC STUDY IN PATIENTS REPORTING MADINA TEACHING HOSPITAL, FAISALABAD - Arsalan Wahid; Farrukh Imran Mian (Journal of University Medical & Dental College, 2013)
ABSTRACT Objective: To assess the prevalence and position of impacted third molars in population of Faisalabad. Methodology: A retrospective study based on orthopantomograms of patients, aged 18-50 years, reported in dental clinics of Madina Teaching Hospital, Faisalabad during the month of January and February 2013 was conducted. Data including age, gender, number of impacted teeth, angulation type, width and depth of impactions was statistically analyzed by Chi-squared test. Teeth positions were analyzed by classifications of Pell & Gregory and Winter. This classification is based on level of impaction, angulations of the impacted third molars and its relationship to the anterior border of the ramus of the mandible. Impactions were analyzed among genders and age groups: group I (18-25 Years) group II (26-35 Years) and group III (36-50 Years) Results: In this study sample; 31%, 30%, 39% subjects were in age groups I, II, and III respectively and 44.1% were males. It was observed that impactions were more prevalent in age group of 18-25 years. Regarding angulations of impacted teeth, maxillary impactions were mostly vertical as compared to mandibular impactions which were mesial and were more prevalent in the age group 18-25 years. Mandibular impactions were more prevalent as compared to maxillary. Impactions were more prevalent in females as compared to males. Maxillary vertical and mandibular mesial were more prevalent in males. Statistical difference between age-groups and among genders was not significant. (p=0.170) Conclusion: This study reports that impacted teeth were more prevalent in females as compared to males in patients reporting to Madina teaching hospital. The age group 18-25 had more impactions as compared to the other two groups and maxillary vertical and mandibular mesial angulations were more prevalent in this study sample